Real-time Dominant Frequency Mapping and Ablation of Dominant-Frequency Sites in Atrial Fibrillation with Left-to-Right Frequency Gradients Predicts Long-Term Maintenance of Sinus Rhythm - Atienza, Felipe (2008)
BACKGROUND: Spectral analysis identifies localized sites of high-frequency activity during atrial fibrillation (AF). We determined the effectiveness of using real-time dominant frequency (DF) mapping for radiofrequency ablation of maximal DF (DFmax) sites and elimination of left-to-right frequency gradients in the long-term maintenance of sinus rhythm (SR) in AF patients. METHODS: DF mapping was performed in 50 pts during ongoing AF (32 paroxysmal, 18 persistent), acquiring a mean of 117±38 points. Ablation was performed targeting DFmax sites, followed by circumferential pulmonary vein isolation. RESULTS: Ablation significantly reduced DFs (Hz) in the LA (7.9±1.4 vs 5.7±1.3, p<0.001), CS (5.7±1.1 vs 5.3±1.2, p=0.006) and RA (6.3±1.4 vs 5.4±1.3, p<0.001) abolishing baseline left-to-right atrial DF gradient (1.7±1.7 vs 0.2±0.9; p<0.001). Only a significant reduction in DFs in all chambers with a loss of the left-to-right atrial gradient after ablation was associated with a higher probability of long-term SR maintenance in both paroxysmal and persistent AF pts. After a mean follow-up of 9.3±5.4 months, 88% of paroxysmal and 56% of persistent AF pts were free of AF (p=0.01). Ablation of DFmax sites was associated with a higher probability of remaining both free of arrhythmias (78% vs 22%; p=0.001) and free of AF (88% vs 30%; p<0.001). CONCLUSIONS: Radiofrequency ablation leading to elimination of LA-to-RA frequency gradients predicts long-term SR maintenance in AF patients.